Marketing Strategy for Beauty Products Based on Halal Values and Emotional Loyalty: A Phenomenological Study of the Wardah and Emina Brands - Azlan Azhari (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study explores the Phenomenology of Consumer Loyalty toward Local Halal Cosmetic Brands, focusing on two leading Indonesian brands: Wardah and Emina. Loyalty to halal brands is understood not merely as repetitive purchasing behavior, but as an emotional, spiritual, and social experience that reflects the identity of modern Muslim women. Within the increasingly competitive beauty industry, local halal brands function as symbols of moral values, national pride, and religious expressions harmonized with contemporary lifestyles. Employing a qualitative phenomenological approach, this research involved twelve Muslim female consumers aged 18–35 who have been active users of Wardah or Emina for at least two years. Data were collected through semi-structured interviews and analyzed using reflective thematic analysis. The analytic process included open coding, identification of essential meanings, and thematic clustering until data saturation was achieved.The findings reveal four key dimensions that form the phenomenological structure of loyalty: (1) spiritual loyalty as a reflection of faith, (2) emotional attachment and trust, (3) social loyalty through Muslim women's solidarity, and (4) pride in authenticity and local cultural values. These findings indicate that loyalty toward halal brands is shaped not only by rational satisfaction but also by internalized religious, affective, and cultural meanings. Theoretically, this study expands the concepts of emotional branding and halal marketing through a phenomenological perspective that positions loyalty as a meaningful lived experience. Practically, the research provides insights for marketers to develop brand communication that is authentic, spiritually grounded, and culturally honest.